1986
DOI: 10.1007/bf02428031
|View full text |Cite
|
Sign up to set email alerts
|

The bialaphos biosynthetic genes ofStreptomyces hygroscopicus: Molecular cloning and characterization of the gene cluster

Abstract: We have isolated and studied the organization of Streptomyces hygroscopicus genes responsible for the biosynthesis of the antibiotic herbicide bialaphos. Bialaphos production genes were cloned from genomic DNA using a plasmid vector (pIJ702). Three plasmids were isolated which restored productivity to S. hygroscopicus mutants blocked at different steps of the biosynthetic pathway. Subcloning experiments using other nonproducing mutants showed that four additional bialaphos production genes were also contained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
131
0
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(134 citation statements)
references
References 18 publications
1
131
0
2
Order By: Relevance
“…Bacterial strains, plasmids and growth conditions Streptomyces lividans prototrophic strain 1326 (Lomovskaya et al, 1972) was grown on NE agar plates (Murakami et al, 1986) or YEME liquid medium containing 34% sucrose (Hopwood et al, 1985). Resistance to thiostrepton was provided by tsr cloned in the streptomycete cloning vector p1I61 (Thompson et al, 1982b).…”
Section: Methodsmentioning
confidence: 99%
“…Bacterial strains, plasmids and growth conditions Streptomyces lividans prototrophic strain 1326 (Lomovskaya et al, 1972) was grown on NE agar plates (Murakami et al, 1986) or YEME liquid medium containing 34% sucrose (Hopwood et al, 1985). Resistance to thiostrepton was provided by tsr cloned in the streptomycete cloning vector p1I61 (Thompson et al, 1982b).…”
Section: Methodsmentioning
confidence: 99%
“…The disrupted mutant grew more slowly than the wild-type strain at 30ЊC on solid NE rich medium (Murakami et al, 1986); this difference was not observed at 37ЊC. At both temperatures, the final colour and sporulation of the mutant colonies were similar to those of wild-type colonies.…”
Section: Growth Of the Hspr Null Mutantmentioning
confidence: 82%
“…and modification systems (Chater and Wilde, 1980), was obtained from the John Innes Culture Collection. S. albus was routinely cultivated on NE plates (Murakami et al, 1986) or in YEME rich liquid medium (Hopwood et al, 1985). When required, thiostrepton and viomycin were used at 25 g ml ¹1 and hygromycin was used at 250 g ml ¹1 .…”
Section: Methodsmentioning
confidence: 99%
“…Antibiotic biosynthesis genes are generally clustered in limited regions in the genome, and the genes conferring resistance to the organism's own products are usually located in or near the gene clusters (Rhodes et a/., 1984;Ohnuki et al, 1985;Chater & Bruton, 1985;Malpartida & Hopwood, 1986;Murakami et al, 1986;Stanzak et al, 1986;Fishman et al, 1987). These facts seem to suggest a tight genetic linkage between antibiotic biosynthesis genes and the resistance genes during the evolution and the horizontal distribution of antibiotic biosynthesis systems.…”
Section: Discussionmentioning
confidence: 99%